The role of classroom interaction in daily writing practice and EFL recount text writing - Saifudin, Ahmad; Kholis, Adhan; Gharamah, Fadhl Mohammed Awadh (Universitas Muhammadiyah Sidoarjo, 2026)
This study investigates how daily writing practice enhances EFL students’ recount text writing through classroom interaction. While previous research has demonstrated the benefits of regular writing practice, most studies have relied on quantitative measures and have paid limited attention to how writing development is mediated through classroom interaction in authentic learning contexts. Addressing this gap, the present study employs a qualitative design to explore both writing development and interactional processes in an Indonesian higher education setting. The study was conducted with 15 third-semester students enrolled in an Intermediate Writing course. Data were collected through classroom observations, students’ written texts, and semi-structured interviews, and were analyzed using thematic analysis to identify patterns of interaction and trajectories of writing development over time. The findings reveal that daily writing practice led to specific improvements in idea elaboration, chronological organization, and control of past tense forms in recount texts. More importantly, classroom interaction, particularly lecturer feedback, peer discussion, and guided questioning, functioned as a mediating mechanism that supported revision, genre awareness, and self-regulated writing. Students gradually shifted from fragmented and formulaic writing to more coherent and reflective recount texts. This study contributes to EFL writing pedagogy by providing qualitative evidence that writing development is not solely driven by practice frequency but also by the quality of interaction embedded within writing activities. It highlights the importance of integrating routine writing practice with interactive, genre-based instruction to foster sustained writing development in higher education contexts.